STRENGTHENING RELIGIOUS MODERATION IN GAMPONG JAWA, LHOKSEUMAWE TO PREVENT CONFLICTS - Munawar Jailani; Dicky Armanda; Danial Danial; Iskandar Iskandar (LP2M Universitas Ibrahimy, 2024)
Religious Moderation is a government initiative aimed at preventing religious-based social conflicts in Indonesia. While religion can bring peace, it has also been used to create divisions within the nation. The service provides education and assistance to prevent religious conflict in Gampong Jawa, Lhokseumawe, a village that is at risk of such conflicts due to tensions between residents who hold different religious beliefs. The program uses Participatory Action Research (PAR) by involving community participation and elements of the leadership of Gampong Jawa, Lhokseumawe, in resolving religious conflicts by strengthening Religious Moderation there. The results of the program include: (1) Increased tolerance and understanding in the community, (2) Resolving religious conflict with empathy and dignity, and (3) promoting awareness of brotherhood Gampong Jawa community, leading to peaceful coexistence despite having different religious views.